Tourism Education Development on the Coastline: Challenges Empirical Study on Islamic Law Province - Suud, Fitriah M.; Rouzi, Kana Safrina; Al-Fairusy, Muhajir; Na’imah, Tri; Harinawati, Harinawati; Yasa, Rawdhah Binti (Jurnal Ilmiah Peuradeun, 2024)
Tourism is one of the contributors to the country’s foreign exchange. Aceh has abundant natural resources. However, natural wealth without adequate human resources cannot be processed as natural resources. Apart from that, the issue of sharia tourism or halal tourism is a debate that affects the smooth running of tourism in Aceh. This research aimed to explore the challenges of developing tourism education in the coastal region of Aceh. The method used was a qualitative descriptive approach. Data collection was carried out using in-depth interviews, focus group discussions, observation, and searching for important documents from both tourism education institutions and agencies related to tourism development in Aceh. The research results found that Aceh has abundant natural resources both in terms of religious tourism, natural tourism, and historical and cultural tourism. However, educational institutions in Aceh to support tourism were still very minimal, especially for universities; Aceh only had one study program at a private university. Meanwhile, the challenge faced in developing tourism education was the lack of professional teaching staff in the tourism sector, apart from educational institutions, which were also still minimal. Likewise, Sharia tourism regulations were not yet legally strong. This research recommends that the government pay more massive attention to Tourism Education Institutions in Aceh.